Maria Vargas Llosa's El hablador as a Discourse of Conquest - José Castro Urioste (Studies in 20th & 21st Century Literature, 2000)
In this article I study how Mario Vargas Llosa's El hablador proposes to deconstruct indigenist narrative and promotes the assimilation of Indian cultures under the model of modernity. In this sense, the novel El hablador is written as a discourse of conquest in which the construction of the self—through the evocation of various oppositions—represents an allegory of modern nation. I begin my article with the analysis of the notion of discourse of conquest, as well as one of its most reiterated images of power, the "civilization-barbarism" dichotomy. I follow this with an analysis of the oppositions through which the representation of the self and the nation are elaborated.
Keywords: conquest; el hablador; María Vargas Llosa; Indian cultures; modernity; novel; discourse of conquest; conquest discourse; power; civilization-barbarism; self; nation